Analisa Pengaruh Komunikasi Pemasaran, Electronic Word of Mouth dan Kualitas Produk Terhadap Keputusan Pembelian IPhone - Sjoraida, Diah Fatma; Simamora, Benget; Diwyarthi , Ni Desak Made Santi; Setianti, Yanti; Aisyah, Siti (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
The advancement of information and communication technology in everyday life has undergone many changes. Smartphone technology is a driver of change, influencing various aspects of society's activities. This research aims to analyze the influence of marketing communications, electronic word of mouth and product quality on iPhone purchasing decisions. The type of research used is quantitative. The independent variables in this research are marketing communications, electronic word of mouth and product quality, the dependent variable is purchasing decisions. The sample was 100 respondents. The method used is quantitative by obtaining data from questionnaires via Google from. The instrument in this research used a questionnaire which was then processed using IBM SPSS version 26 software. Data analysis used multiple linear regression. The partial results of this research show that marketing communications, electronic word of mouth and product quality have a significant positive effect on purchasing decisions. Simultaneously, the research results show that marketing communications, electronic word of mouth and product quality have a significant positive effect on purchasing decisions.